Powertrain parameter matching and optimal design of dual-motor driven electric tractor - Chen, Yanni; Xie, Bin; Du, Yuefeng; Mao, Enrong (International Journal of Agricultural and Biological Engineering, 2019)
The rationality of powertrain parameter design has a significant influence on the traction performance and economic performance of electric tractor. At present, researches on powertrain parameter design mainly focus on electric vehicles, and electric agricultural machinery draw much less attention. Therefore, a method of powertrain parameter matching and optimization design for electric tractor was proposed in this paper, which was based on dual-motor coupling drive mode. The particle swarm optimization (PSO) algorithm based on mixed penalty function was used for parameter optimization. Parameter optimization design was programmed using MATLAB. A simulation dynamic model with optimization design variables of electric tractor powertrain was established based on MATLAB/Simulink. Compared with the simulation results before optimization, the objective functions were optimized and the traction performance of electric tractor was improved, which indicated the effectiveness of the proposed method. Keywords: electric tractor, parameter matching design, parameter optimization design, powertrain, traction performance DOI: 10.25165/j.ijabe.20191201.3720 Citation: Chen Y N, Xie B, Du Y F, Mao E R. Powertrain parameter matching and optimal design of dual-motor driven electric tractor. Int J Agric & Biol Eng, 2019; 12(1): 33–41.